2017
DOI: 10.1002/adma.201701323
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Responsive Chiral Nematic Cellulose Nanocrystal/Poly(ethylene glycol) Composite Films with Uniform and Tunable Structural Color

Abstract: The fabrication of responsive photonic structures from cellulose nanocrystals (CNCs) that can operate in the entire visible spectrum is challenging due to the requirements of precise periodic modulation of the pitch size of the self-assembled multilayer structures at the length scale within the wavelength of the visible light. The surface charge density of CNCs is an important factor in controlling the pitch size of the chiral nematic structure of the dried solid CNC films. The assembly of poly(ethylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
441
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(461 citation statements)
references
References 62 publications
16
441
4
Order By: Relevance
“…Indeed, if the onset of the first degradation process is estimated, an increase of 10 • C, 16 • C and 21 • C on the composite system with 30 wt.% (T = 154 • C), 40 wt.% (T = 160 • C) and 50 wt.% (T = 165 • C) respectively, is observed when compared with the neat CNCs (T = 144 • C). Similar tendencies were observed in composite systems of CNCs/PEG [14]. In this work, the authors related this thermal stability to the formation of a uniform PEG layer onto the surface of the CNCs protecting them from degradation.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Indeed, if the onset of the first degradation process is estimated, an increase of 10 • C, 16 • C and 21 • C on the composite system with 30 wt.% (T = 154 • C), 40 wt.% (T = 160 • C) and 50 wt.% (T = 165 • C) respectively, is observed when compared with the neat CNCs (T = 144 • C). Similar tendencies were observed in composite systems of CNCs/PEG [14]. In this work, the authors related this thermal stability to the formation of a uniform PEG layer onto the surface of the CNCs protecting them from degradation.…”
Section: Resultssupporting
confidence: 66%
“…For instance, Yao et al were able to retain structural colouration after the addition of polyethylene glycol (up to 50wt.% CNC/PEG) to the CNCs suspension. The final product was humidity-responsive, since exposure to humidity increases the pitch value of the films in a reversible process, and became flexible as the authors increased the PEG content in the composite system [14]. Similar phenomena were reported when glycerol was added to the CNCs suspension by He et al [15] and by Xu et al [16].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Because of the structure, the films behave as 1D photonic crystals, reflecting circularly polarized light having the same sense as the cholesteric screw orientation . This property of CNCs is attractive for producing iridescent films with many potential applications …”
Section: Methodsmentioning
confidence: 99%
“…[22] Khan et al incorporated chiral nematic CNCs into thermoset polymers;these materials showed responsive color changes,b ut were not flexible. [23] Other strategies to make flexible CNC-containing materials that show structural color include the incorporation of surfactants, [24] polymers [25][26][27] and other additives [28] to produce flexible CNC films.H owever, these materials do not exhibit responsive color.…”
mentioning
confidence: 99%